Protective effects of Purendan superfine powder on retinal neuron apoptosis in a rat model of type 2 diabetes mellitus★ - Dong, Zhijun (Neural Regen Res, 2012)
This study sought to investigate the effects of Purendan superfine powder comprised of Momordica charantia, Radix Ginseng, and Radix Salviae Miltiorrhiae on neuronal apoptosis and expression of bcl-2, bax, and caspase-3, which are retinal apoptosis-associated factors in rats with diabetes mellitus induced by continuous intraperitoneal injection of streptozotocin. The results showed that Purendan superfine powder could upregulate the expression of bcl-2 protein and mRNA, and downregulate the expression of bax and caspase-3 in the retina of diabetes mellitus rats. In addition, Purendan superfine powder was shown to reduce the number of apoptotic neurons. Our experimental findings indicate that Purendan superfine powder can inhibit neuronal apoptosis in the retina of diabetes mellitus rats and has protective effects on diabetic retinopathy.